Effect of Low-Quality Calcined Clay on the Suppression of the Alkali–Silica Reaction - Daria Jóźwiak-Niedźwiedzka; Roman Jaskulski; Kinga Dziedzic; Aneta Antolik (Materials Proceedings, 2023)
This article presents the results of an experimental investigation into the mitigation of the alkali–silica reaction (ASR) resulting from using low-grade clay calcined at 850 °C. The clay used in the experiment was domestic clay with an Al2O3 content equal to 26% and a SiO2 content of 58%. The performance of calcined clay in ASR mitigation was evaluated according to ASTM C1567 using reactive aggregates. The control mortar mixture consisted of 100% Portland cement (Na2Oeq = 1.12%) binder and reactive aggregate. The test mixtures used the same reactive aggregate and binders, in which part of the cement was replaced with either 10%, 20% or 30% calcined clay. The microstructure of specimens was examined on the polished sections using a scanning electron microscope (SEM) operated in the backscattered mode (BSE). The results of expansion obtained from the mortar bars made with the reactive aggregate showed that replacing cement by calcined clay reduced their expansion, with the level of expansion decreasing with the increase in the level of cement replacement.